Economic Perspectives on Corporate Social Responsibility - Kitzmueller, Markus; Shimshack, Jay (Journal of Economic Literature, 2012)
This paper synthesizes the expanding corporate social responsibility (CSR) literature. We define CSR from an economic perspective and develop a CSR taxonomy that connects disparate approaches to the subject. We explore whether CSR should exist and investigate conditions when CSR may produce higher welfare than other public good provision channels. We also explore why CSR does exist. Here, we integrate theoretical predictions with empirical findings from economic and noneconomic sources. We find limited systematic empirical evidence in favor of CSR mechanisms related to induced innovation, moral hazard, shareholder preferences, or labor markets. In contrast, we uncover consistent empirical evidence in favor of CSR mechanisms related to consumer markets, private politics, and public politics. (JEL D21, L21, M14)